Analisis Metode Pembelajaran Interaktif Untuk Siswa Sekolah Dasar (Studi Kasus SD Negeri 162 Aek Marian) - Afrijal Mahmud; Syahrial (CV. ITTC INDONESIA, 2024)
Education is an important foundation in shaping individual character and abilities from an early age. At the elementary school (SD) level, education focuses not only on the transfer of knowledge, but also on developing students' social, emotional and cognitive skills. One approach that is increasingly being applied to achieve this goal is interactive learning methods. Interactive learning is an increasingly popular approach in education, especially at the elementary school (SD) level. The aim of the research is to analyze the interactive learning methods implemented at SD Negeri 162 Aek Marian and evaluate their impact on the student learning process. Qualitative research methods, research results, Implementation of interactive learning methods at SD Negeri 162 Aek Marian shows positive results, although there are several obstacles that need to be overcome. Among them, limited facilities, not all teachers have the skills and knowledge needed to implement interactive learning methods effectively. Students have different abilities and learning styles. Adapting interactive learning methods to suit all students can be a challenge.